Existence and Decontamination of HVC, Infectious Enteric Bacteria and Parasites in Sewaged Soils - Hassanain, Mohey A.; Hassanain, Nawal A.; Hobballa, Esam A.; Abd- El Zaher, Fatma H.; Saber, Mohamed Saber M. (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
A surface sample representing a high contaminated loamy sand soil irrigated with sewage effluent since 30 years and was cultivated with artichoke was collected from Abu-Rawash sewage farm. The existence of HVC, enteric infectious bacteria and parasites in sewaged soil found to be negative for the forward and positive for the latter's. Out of the 30 samples separated from the sewaged soil sample, only 3 samples contained parasitic fauna of developed and undeveloped Ascaris (10%) and five samples contained Entamoeba coli. Results showed that the number of Ascaris eggs/gm soil was 0.017 and the number of E. coli/gm was 0.26. Decontamination of soil parasites was effective using either calcium hypochlorite or potassium permanganate. Salmonella, Vibrio and Campelobacter were detected in the high contaminated sewaged soil and survived for 120 days in the sewaged soil under all control and bioremediated treatments irrigated with either sewage effluent or water.